LEARNING MOTIVATION OF ELEMENTARY SCHOOL CHILDREN: IS IT POSSIBLE TO BE INCREASED USING THE TEAMS GAMES TOURNAMENT MODEL? - Cahyani, Nurma; Mustadi, Ali (UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to increase learning motivation in social studies using the Teams Games Tournament (TGT) model. It used the Classroom Action Research (CAR) design by Kemmis and Mc. Taggart. The subjects were elementary school students in grade IVB. The data were analyzed using quantitative descriptive analysis. In implementing the TGT model steps, ice-breaking was presented before learning and on the sidelines of games and tournaments not to get bored. The results showed that in the pre-cycle, the student's learning motivation reached 47%. Then, in the first cycle, the student’s learning motivation increased to 68%, while in the second cycle, it reached 94%. Therefore, in the second cycle, the motivation had reached the specified criteria of ≥75%, indicating that the children have high learning motivation. Thus, it can be concluded that the Teams Games Tournament model can increase student’s learning motivation in social studies.